PENGARUH KUALITAS PELAYANAN DAN PERSEPSI NILAI TERHADAP KEPUASAN UNTUK MENINGKATKAN WORD OF MOUTH PARTY PLANNER - Alexandra, Alicia; Suprapti, Ni Wayan Sri (E-Jurnal Manajemen; Vol 8 No 3 (2019)DO - 10.24843/EJMUNUD.2019.v08.i03.p04, 2019)
This study aims to determine the effect of service quality and perceived value on customer satisfaction to improve word of mouth for party planner service users. Data was taken using a questionnaire from 107 respondents in Denpasar City who had used the service at least once in the last two years. Data is processed using regression analysis. The results of the study found that service quality and value perception had a positive and significant effect on customer satisfaction. In addition, customer satisfaction also has a positive and significant effect on word of mouth. These results indicate that to improve positive word of mouth, the company is expected to be able to maintain or increase customer satisfaction. Customer satisfaction can be maintained or improved by maintaining or improving service quality and perceived value.